Chronification of metastatic leiomyosarcoma in 9 lines of therapy by precision oncology: a case report and review of the literature - Klein, Christian R.; Koob, Sebastian; Tischler, Verena; Heine, Annkristin; Brossart, Peter; Feldmann, Georg; Mayer, Karin (Frontiers in Oncology, 2025)
Leiomyosarcoma is a malignant soft tissue tumor that still has a very poor prognosis in the metastatic stage, often lasting only several months. In addition to surgery and radiotherapy, the conventional treatment of this tumor entity is determined by chemotherapeutic regimes. Apart from anti-angiogenetically effective substances, hardly any targeted therapy options have been established. Here, we report the case of a 70-year-old man with metastatic leiomyosarcoma, who was able to be chronified by nine lines of oncological therapy over a period of four years, in addition to partial tumor resection and radiotherapy. The survival reported here is far greater than would be expected under approved standard therapy. Key to the long-term treatment of this patient was comprehensive pancancer panel sequencing (CCP, next-generation sequencing of genomic DNA) of the cancer tissue to search for molecular targets. This detected a loss-of-function mutation in a homologous recombination repair (HRR) gene, enabling treatment with the PARP inhibitor olaparib. Another special feature was the addition of the alkylating cytostatic agent temozolomide; the effectiveness of this combination therapy has so far only been shown for uterine leiomyosarcoma, but also proved to be an effective therapeutic strategy in the case of a male patient reported here. Despite high cumulative doses of previously applied chemotherapy, the targeted oncological treatment was tolerable and effective. The case report shows the high value of systematic molecular sequencing of cancer tissue and presentation in molecular tumor board for identification of molecular target structures for optimized palliative systemic therapy of metastatic leiomyosarcoma. In addition, the case report demonstrates that the combination therapy olaparib/temozolomide may also be an effective treatment approach for nonuterine leiomyosarcoma with HRR loss of function.